Penerapan "Spirit" Man Jadda Wajada Untuk Meningkatkan Hasil Belajar Pokok-Pokok Isi Ajaran Al-Qur’an di MAN 1 Metro - Gufron, Gufron (Tarbawiyah Jurnal Ilmiah Pendidikan, 2021)
This article describes the concept of "Man Jadda Wajada" which is an acronym for Man (Mengoptimalkan Pembelajaran Saintifik) with Jadda (Jaringan Dalam Diskusi dan Arahan) and Wajada (Wadahi Jangkauan dan Penugasan) by communicating the results of assignments and discussing them. This concept was implemented through two cycles of classroom action research (CAR) which was conducted on 35 students of class X IPS 3 in the odd semester of the 2019/2020 Academic Year of Madrasah Aliyah Negeri (MAN) 1 Metro City. From the two CAR cycles that have been carried out, the learning outcomes of the main contents of the teachings of the Qur'an for class X IPS 3 MAN 1 Metro students can be improved through the application of "Man Jadda Wajada". The changes in spiritual attitudes from cycle I to II which experienced a significant increase, that the distribution of the predicate of spiritual attitude and honesty of students showed a change in spiritual attitude, namely there were no more less and enough predicates, 80% good predicates and 20% very good predicates. Meanwhile, the change in honesty attitude from cycle I to II also experienced the same thing, namely there were no less and enough predicates, 51% were good and 49% were very good. As for the change in the final value from cycle I to II, the highest was from 79.40 to 89.40 or an increase of 10.00, and the lowest was from 48.00 to 71.00 or an increase of 23.00, the average started from 64.97 to 75 .04 increased by 10.1. In line with this change, that in the second cycle, there is no less predicate, 6% predicate enough, 9% good predicate, but there is no very good predicate.